Effect of protein adsorption on bioelectrochemistry of electrospun core-shell MWCNTs/gelatin-Hb nanobelts on electrode surface. (September 2020) - Deng, Z.X.; Tao, J.W.; Zhao, L.J.; Zhang, W.; Wang, Y.B.; Mu, H.J.; Wu, H.J.; Xu, X.X.; Zheng, W.
Graphical abstract: Highlights: Electrospinning is a simple and valid technique to modify the electrode surface. The electrospun core-shell MWCNTs/gelatin-Hb nanobelts was constructed on electrode. Direct electron transfer between the Hb and electrode can be still achieved after the nanobelts adsorbed protein. Catalysis of H2 O2 can be still achieved after the nanobelts adsorbed protein. The construct biosensor displayed high reproducibility, stability and selectivity after protein adsorption. Abstract: Implantable electrochemical biosensor is one powerful tool for the accurate and reliable measurements of small molecules in vivo. However, the electrode is inevitably subjected to the protein adsorption when implanted into the living animals, affecting the sensitivity and stability of biosensor. Herein, we designed the multi-walled carbon nanotubes/gelatin-hemoglobin (MWCNTs/gelatin-Hb) core-shell nanobelts constructed on glassy carbon electrode (GC) using the one-step electrospinning technique for studying the effect of protein adsorption on the electrode surface properties. The results of the water contact angle and the scanning electron microscopy (SEM) showed that the electrospun core-shell MWCNTs/gelatin-Hb nanobelts present hydrophilic and certain anti-protein adsorption properties. Direct electron transfer between the Hb molecules in the electrospun core-shell nanobelts and electrode and catalysis of hydrogen peroxide (H2 O2 ) can be still achieved after the electrospun core-shell MWCNTs/gelatin-Hb nanobelts adsorbed protein. Moreover, compared with before protein adsorption ( K m app =0.0155 mmol/L), the electrospun core-shell MWCNTs/gelatin-Hb nanobelts after protein adsorption still displayed high biological afﬁnity to H2 O2 ( K m app =0.0382 mmol/L). The constructed H2 O2 biosensor by using the electrospun core-shell MWCNTs/gelatin-Hb nanobelts showed high sensitivity, great reproducibility and stability after protein adsorption. This study provides a novel design and an effective platform for the development of implantable electrochemical biosensors.